Inequality of opportunity in educational achievements: Cross-country and intertemporal comparisons - Patrizia Luongo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper evaluates fairness in educational achievements through the ordered pair (WEEOp, IEOp) whose components provide: (i) A measure of social welfare which accounts for the achievement of less-advantaged pupils and (ii) a synthetic index of inequality in educational opportunities. Students' test scores from the Programme for International Students Assessment PISA, 2003, 2006, 2009, and 2012 are exploited to perform a cross-country and intertemporal comparison of fairness in education. The cross-country comparison shows that none of the countries outperform in both components of fairness, whereas the intertemporal comparison shows that few countries have moved towards a greater degree of equality of opportunity all the while improving the performance of the less-advantaged students.
Keywords: I24; I31; 330; inequality of opportunity; educational achievements; Programme for International Students Assessment survey